FOCAL MECHANISMS OF EARTHQUAKES IN THE SUBDUCTION ZONE OF THE WESTERN PACIFIC PLATE - N. A. Bushenkova; O. A. Kuchay (Геодинамика и тектонофизика)
Deformation features of the subducting Pacific lithospheric plate are considered according to the data on earthquake focal mechanisms. The territory includes the convergent boundaries between the Pacific Plate and the North American (in the Aleutian arc region), the Okhotsk, the Eurasian and the Philippine plates.It has been shown that the angle of subducting Pacific Plate in the Aleutian subduction zone affects the focal mechanisms of earthquakes that occurred in the upper, 35 km part of the oceanic plate in the zone of its bending. There occur normal-fault earthquakes at a steep-angle subduction and rare thrust earthquakes at a shallow-angle subduction. The azimuthal orientation of P-axes of the focal mechanism solutions in the upper (1–70 km) contact zone corresponds to the Pacific Plate displacement vector when the plate fragments are subducting west-northwestwards. There occurs a change in azimuthal orientation of the compression axes in the subducting plate at a depth of more than 70 km: the axes occupy different azimuthal sectors showing difference in the orientation of their slope, with the orientations of the T-axes become multidirectional.The calculation of seismotectonic deformations was carried out based on the data on focal mechanisms of 7768 earthquakes. It was revealed that the Exx and Ezz deformation fields are the most homogeneous at depths of 1–70 km. The pattern of seismotectonic deformations changes abruptly for deep parts of the subducting plate (105–200, 200–400, and 400–700 km), there are observed heterogeneous deformation fields Exx, Eyy and Еzz with alternating episodes of extension and shortening.There has been proposed the author’s scheme of the influence of the upper mantle convection structure on the geometry of the subducting plate (slab) as a potential catalyst for the processes responsible for the separation of seismic activity zones and the change of earthquake types with depth and in different parts of the extended subduction zone.